2014
DOI: 10.5005/jp-journals-10001-1192
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Lymphatic Metastasis to Neck Nodes Level IIb in Neck Dissection for Head and Neck Cancers: A Retrospective Study

Abstract: Introduction: Selective neck dissection (SND) is performed to prevent head and neck cancers metastasis. We tried to determine the incidence of level IIb lymph nodes metastasis and it is associations in head and neck cancers for selection of patients requiring SND. Materials and methods:A retrospective study was conducted on 57 patients who underwent surgical removal of the head and neck tumor by 84 neck dissections. Fisher exact test was used to measure the association between positive IIb nodes and the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…3 As described by the previous researchers also, 3,17 the presence of lymph node metastasis in the neck of the patients with cancers of head and neck region is an important prognostic determinant in staging cancers and in treatment planning for such patients. Al Zahrani et al 1 reported most of the tumors were located in the oral cavity, 43 (75.4%) followed by the larynx 7 (12.3%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 As described by the previous researchers also, 3,17 the presence of lymph node metastasis in the neck of the patients with cancers of head and neck region is an important prognostic determinant in staging cancers and in treatment planning for such patients. Al Zahrani et al 1 reported most of the tumors were located in the oral cavity, 43 (75.4%) followed by the larynx 7 (12.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these cancers are squamous cell carcinomas (SCCs) and they usually metastasized locally to the cervical lymph nodes. 1 Oral cancer is the sixth most common cause of cancerrelated deaths worldwide. 2 In the subcontinent scenario oral cancer is the second most common cancer.…”
Section: Introductionmentioning
confidence: 99%